Abiotic and biotic factors affecting Rhagoletis mendax [Diptera :Tephritidae] populations in eastern Canadian lowbush blueberry fields - Geddes, P.S.; LeBlanc, J.-P.R.; Yule, W.N. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1992)
An investigation was carried out in Nova Scotia and New Brunswick, Canada, to identify natural regulatory factors, such as soil acidity and weed incidence, that could influence the occurrence of blueberry maggot (Rhagoletis mendax) populations in commercial lowbush blueberry fields (Vaccinium angustifolium). Over the range observed, the soil acidity had no detectable influence on the distribution and mortality of R. mendax larvae and pupae. Adult migrational patterns were affected by the cultural practice of burning on alternate years causing the emerging adults of burned fields to move toward sareasin production. There was also a positive correlation between the growth intensity of indigenous weeds and blueberry maggot infestation levels.